Extracellular matrix-derived hydrogels for dental stem cell delivery - Viswanath, Aiswarya; Vanacker, Julie; Germain, Loic; Leprince, Julien G.; Diogenes, Anibal; Shakesheff, Kevin M.; White, Lisa J.; des Rieux, Anne (Wiley, 2016)
Decellularised mammalian extracellular matrices (ECM) have been widely accepted as an ideal substrate for repair and remodelling of numerous tissues in clinical and pre-clinical studies. Recent studies have demonstrated the ability of ECM scaffolds derived from site-specific homologous tissues to direct cell differentiation. The present study investigated the suitability of hydrogels derived from different source tissues: bone, spinal cord and dentine, as suitable carriers to deliver human apical papilla derived mesenchymal stem cells (SCAP) for spinal cord regeneration. Bone, spinal cord and dentine ECM hydrogels exhibited distinct structural, mechanical and biological characteristics. All three hydrogels supported SCAP viability and proliferation. However, only spinal cord and bone derived hydrogels promoted the expression of neural lineage markers. The specific environment of ECM scaffolds significantly affected the differentiation of SCAP to a neural lineage, with stronger responses observed with spinal cord ECM hydrogels, suggesting that site-specific tissues are more likely to facilitate optimal stem cell behaviour for constructive spinal cord regeneration